Thoughts Of Moral Education Studi The Comparison of Thoughts Between Ibn Qayim al-Jauziyah and Imam al-Ghazali - Muhammad Barid; Mahsun Jayadi (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2020)
The purpose of this research is  to  describe,knowing  the comparison of the concepts of moral  education and knowing the actualization of the moral educational thinking of Imam al-Ghazali and Ibn Qayim al-Jauziyah when applied in the practice of education.. Penelitian is library research. Using  two types  of  data sources,  namely; Primary, and  Secondary Sources,  In data collection select and classify existing data based on association with research objects. Furthermore, data processing is done by descriptive analysis, then done analysis and interpretation of existing data. Comparative analysis will also be used in this study. This analysis is used to compromise the opinions of the two figures, so that with this comparison is made a generalization of applied theories. Untuk achieve the goal of research, a philosophical analysis of the thinking of a person in a certain time inthe past, methodologically, this research will use a historical approach. Thislanguage concluded  first      imam al-Ghazali and Ibn Qayim al-Jauziyah both set out their thoughts in criticizing the deviant and harmful filusuf thinking of the people. So they are both in formulating their thoughts together asyou  cling to islamic values. Both  Imam al-Ghazali and Ibn Qayim al-Jauziyah both used the talak measure of the Qur'an and al-Hadith..  The  third in educating imam al-Ghazali's morality is more focused on the individual himself, which is through the way of mujahadah, while Ibn Qayim argues that the role of teachers can help in educating morals. The  Four Directions and the orientation of education between Imam al-Ghazali and Ibn Qayim both aim to print the perfect human being (human kamil) in order to achieve real happiness so as to be able to live happily in this world and the hereafter. The  five Pemikiran moral educationIbn Qayim and Imam al-Ghazali both emphasized on the education of children, the sixth Blend of moral education Imam al-Ghazali and Ibn Qayim al-Juziyah is expected to be able to print human beings who are sincere karimah so as to face the challenges of the times.